THE PREVALENCE OF SLEEP DISORDERS AMONG SUBSTANCE ABUSERS ADMITTED TO DRUG DE-ADDICTION UNIT AT ERADAH AND MENTAL HEALTH COMPLEX, TAIF, SAUDI ARABIA - Siddiqui, Javed Ather; Eldaous, Ali Mahmoud; Qureshi, Shazia Farheen; Alotaibi, Hani Matrok; Hamdan, Sameh; Almahqori, Ali Ahmed (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction – Public health is affected by substance abuse, which is associated with high mortality and morbidity rates. A person who suffers from substance use disorder is more likely to suffer from insomnia. The health and social well-being of individuals and communities are adversely affected by these substances. Therefore, in recent years, research has become increasingly interested in the connection between substance abuse and sleep. The main objectives of this study are to evaluate the prevalence of sleep disorders; to investigate any relationship between sleep disorder and impact of sleep on daily functioning; to evaluate the socio-demographic profile; to find out the sleep disturbances caused by specific substances of abuse and to elucidate the relationship of sleep disturbances and substance use. Methods – Substance abusers with sleep disorders admitted to the hospital who met the inclusion and exclusion criteria were included in this study. The data was collected using sociodemographic information and a sleep 50 scale to interview subjects who are active substance abusers. The data was analyzed using SPSS software. Results – A high prevalence of sleep disorder was found in male group of patients. Among the 653 substance users, 643 (98.47%) were male and 10 (1.53%) were female. According to the survey, 284 (43.50%) of the participants reported abusing substances during their 25 to 30 years of age, following by 215 (32.92%) during their 18 to 24 years of age. In this study, various sleep disorders among drug addicts were systematically evaluated. Discuss – The prevalence of various sleep disorders in this population along with the prevalence in general population in parenthesis. These are as follows, sleep disorder was noted in 475 (72.74%) of the subjects, and 178 (27.26%) had without sleep disorder in Substance Abusers. Insomnia symptoms were highly prevalent 351(73.89%), followed by restless leg were reported in 157 (33.05%) of the subjects and lowest in circadian rhythm disorder 8 (1.68%). Conclusion – The incidence of substance abuse has grown dramatically over the last few decades and is affecting every aspect of society. Due to their wide availability, amphetamine and cannabis abusers were the most prevalent in our study, and sleep disorders, including insomnia, were the most prevalent.